The relationship between vitamin A and ferritin towards malondialdehyde level among Javanese male smokers - Ahmad Hamim Sadewa, Ajeng Viska Icanervilia Sunarti (Universitas Gadjah Mada, 2012)
Cigarette smokes produce a large number of oxidants and promote secretion of ferritin byalveolar macrophages which are potential to encourage the lipid peroxidation. Malondialdehyde(MDA) is used as a parameter of lipid peroxidation. The study was aimed to evaluate therelationship between blood level of vitamin A and ferritin and MDA among Javanese malesmokers. Sixty men who lived in Purworejo District, Central Java, Indonesia comprising 30smokers as case group and 30 nonsmokers as control group were involved in this study. Bloodsample was obtained from cubiti vein and then centrifuged to obtain plasma or serum. Blood levelsof vitamin A, ferritin and MDA were measured by HPLC, ELISA and spectrophotometric methods,respectively. The result showed that the blood vitamin A, ferritin, and MDA levels in smokers were25.09±9.51μg/dL, 35.50±24.17ng/dL, 1.15±0.42μg/L, respectively, whereas in non smokers, theywere 26.11±9.19 μg/dL, 38.60±15.25 ng/dL, 1.06±0.50 μg/L, respectively. Therewas no significantdifference of the blood vitamin A, ferritin, and MDA levels between smokers and the non smokers(p>0.05). The linear regression analysis indicated that there was negative relationship betweenblood vitamin A and MDA levels although it was not significant (p=0.052), while blood ferritin andMDA levels had a significantly positive relationship (p=0.010). In conclusion, the low level of bloodvitamin A among cigarette smokers does not lead to high blood MDA level, while high level of bloodferritin among smokers leads to high blood MDA level.Keywords: vitamin A - ferritin - malondialdehyde - cigarette - smokers